Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil - Martins, André L.; Domahovski, Alexandre C. (Zootaxa, 2017)
Gonatopus amazonicus Olmi is redescribed and illustrated based on a single female reared from an adult parasitized leafhopper belonging to the genus Frequenamia DeLong (Cicadellidae, Deltocephalinae), collected by sweeping on Eugenia uniflora L. in Southern Brazil. This female emerged 46 days after pupation.